Common feline problem behaviors: Urine spraying. Issue 3 (March 2019) - Horwitz, Debra F
Practical relevance: Urine spraying (synonymous terms include urine marking or scent marking) is commonly described as urine deposited on vertical surfaces while the cat is in a standing position. With the increasing trend of keeping cats indoors in some countries and the potential resultant increase in frustration-related behaviors, urine spraying may occur in the home. Although also a normal feline behavior, it is usually not deemed acceptable when the cat targets household possessions. Urine spraying is a common behavioral complaint that practitioners receive from cat owners and has the potential to disrupt the human–cat bond. In fact, feline elimination issues are a frequent reason cited by owners when they relinquish their cats to shelters and rescue organizations. Clinical challenges: While the location of the deposited urine should be diagnostic, this is not always the case. Urine marking can occur on horizontal surfaces, thus complicating the diagnosis. Urine spraying by intact males and females is used to signal availability for mating but the behaviour can also be exhibited by neutered animals. Multiple factors including medical problems can trigger the onset and maintenance of urine spraying, and correct identification of these is necessary for treatment to be most successful. Evidence base: This review draws on information from multiple studies that have been published on the normal aspects of urine spraying in cats, the frequency as reported by owners, the relationship of urine spraying to intercat aggression and various treatment options including behavior modification, pheromone therapy and use of psychoactive medication.